Analisis Sistem Kompensasi pada UKM XYZ Menggunakan Metode Tumpang Tindih (Overlapping) - Dila Rosalia Amanda; Hafiz Syaikhul Musthafa; Naila Shofia Khansa; Rizka Maulidia Husna; Salsabila Hana Afridhayanti (Jurnal Kewirausahaan Cerdas dan Digital, 2024)
One of the crucial components in human resource management is a fair and appropriate compensation system. This research analyzes the compensation system at UKM XYZ in Bogor Regency using the Overlapping method. Analysis methods include descriptive analysis, job analysis, given system method analysis, and salary mapping analysis with the Overlapping method. The results showed that the initial salary of UKM XYZ was not ideal because the mid-to-mid value comparison was still greater than the spread value. After revamping with the Overlapping method, a new compensation structure was obtained with an increase in operating costs of 6.75%. A competitive and fair compensation system is expected to improve employee motivation, productivity, and performance as well as the competitiveness of UKM XYZ in the industry. This research provides recommendations for UKM XYZ to implement a new compensation system based on the Overlapping method to meet the needs of the company and employees.